2017
DOI: 10.1016/s2352-3018(17)30053-x
|View full text |Cite
|
Sign up to set email alerts
|

Durability of viral suppression with first-line antiretroviral therapy in patients with HIV in the UK: an observational cohort study

Abstract: SummaryBackgroundThe length of time that people with HIV on antiretroviral therapy (ART) with viral load suppression will be able to continue before developing viral rebound is unknown. We aimed to investigate the rate of first viral rebound in people that have achieved initial suppression with ART, to determine factors associated with viral rebound, and to use these estimates to predict long-term durability of viral suppression.MethodsThe UK Collaborative HIV Cohort (UK CHIC) Study is an ongoing multicentre c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
50
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 26 publications
15
50
1
Order By: Relevance
“…Our study also demonstrates that other factors such as duration of ART and adherence to ART were associated with the viral load. Similar to our research, longer duration on ART and high adherence to ART drugs were found to be associated with viral suppression or a lower level of viral load in different studies [25,[30][31][32][33]. This association implies the effectiveness of ART in improving the immune system.…”
Section: Discussionsupporting
confidence: 88%
“…Our study also demonstrates that other factors such as duration of ART and adherence to ART were associated with the viral load. Similar to our research, longer duration on ART and high adherence to ART drugs were found to be associated with viral suppression or a lower level of viral load in different studies [25,[30][31][32][33]. This association implies the effectiveness of ART in improving the immune system.…”
Section: Discussionsupporting
confidence: 88%
“…VL = viral load; ART = antiretroviral therapy; AIC = Akaike information criterion; the lower the value of the AIC, the better model fit. 1,2 Main predictors VLs at 1 and 3 month fitted on logarithmic scale (see methods). 2 Adjusted for age (continuous), ethnicity and gender/likely risk for HIV acquisition, and treatment regimen.…”
Section: Resultsmentioning
confidence: 99%
“…The second approach to cost estimation (model 2) used the same HARS data to inform when a person entered the model from diagnosis to ART initiation. However, subsequent changes to the ART regime were based on the annual rate of primary ART failure as reported by the UK CHIC cohort study . The annual rate of primary viral rebound was based on data for 16 101 persons who started ART between January 1998 and May 2013 .…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent changes to the ART regime were based on the annual rate of primary ART failure as reported by the UK CHIC cohort study . The annual rate of primary viral rebound was based on data for 16 101 persons who started ART between January 1998 and May 2013 . In those with primary viral rebound following first‐line ART, model 2 assumed that the proportional distribution of those given second‐ or subsequent‐line or complex ARV followed the proportional distribution of patients by treatment complexity level as recorded in HARS.…”
Section: Methodsmentioning
confidence: 99%